Hubungan Kesepian dengan Kualitas Hidup Lansia di Wilayah Kerja Puskesmas Sungai Lokan Kab. Tanjung Jabung Timur - Sekiawati; Subang Aini Nasution; Sri Mulyati (Universitas Adiwangsa Jambi, 2026)
Background: Loneliness is one of the psychosocial problems commonly experienced by the elderly and can have an impact on their quality of life. Elderly individuals who experience loneliness tend to have limited social interactions, which affect their physical, psychological, and social conditions. This study aimed to determine the relationship between loneliness and quality of life among the elderly in the working area of Sungai Lokan Public Health Center. Methods: This study used a quantitative method with a cross-sectional design. The population in this study consisted of all elderly individuals in the working area of Sungai Lokan Public Health Center, with a total sample of 61 respondents selected using a sampling technique (as appropriate). The instruments used were the UCLA Loneliness Scale to measure loneliness and WHOQOL to measure quality of life. Data were analyzed using univariate and bivariate analysis with the Chi-Square test. Results: The results showed that most respondents had poor quality of life (34 respondents; 55.7%) and high levels of loneliness (24 respondents; 39.3%). The bivariate analysis indicated a significant relationship between loneliness and quality of life among the elderly, with a p-value of 0.000 (p < 0.05). Conclusion:. there is a significant relationship between loneliness and quality of life among the elderly, where higher levels of loneliness are associated with poorer quality of life